Algorithmic systems: The consent is in the detail? - Alexandra Giannopoulou (Internet Policy Review, 2020)
Applications of algorithmically informed decisions are becoming entrenched in society,with data processing being their main process and ingredient. While these applications areprogressively gaining momentum, established data protection and privacy rules have struggledto incorporate the particularities of data-intensive information societies. Consequently, there isa misalignment created between algorithmic processing of personal data and the correspondingregulatory frameworks since they both strive for meaningful control over personal data.However, the challenges to the traditional role and the concept of consent are particularlymanifest. This article examines the transformation of consent in order to assess how the conceptin itself as well as the applied models of consent can be reconciled to correspond not only tocurrent data protection normative frameworks but also to algorithmic processing technologies.This particularly pressing area of safeguarding a fundamental aspect of individual control overpersonal data in the algorithmic era is interlinked with practical implementations of consent inthe technology used. Moreover, it relates to adopted interpretations of the concept of consent, tothe scope of application of personal data, as well as to the obligations enshrined in them. Whatmakes consent efficient as a data protection tool? Can its previous glory be maintained withinthe current techno-legal challenges?
Keywords: 300; Algorithms; GDPR; Data protection; Consent